2015
DOI: 10.1038/npp.2015.210
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Treatment Leads to Enhanced Fear Extinction and Dynamic Fkbp5 Regulation in Amygdala

Abstract: Posttraumatic stress disorder (PTSD) is both a prevalent and debilitating trauma-related disorder associated with dysregulated fear learning at the core of many of its signs and symptoms. Improvements in the currently available psychological and pharmacological treatments are needed in order to improve PTSD treatment outcomes and to prevent symptom relapse. In the present study, we used a putative animal model of PTSD that included presentation of immobilization stress (IMO) followed by fear conditioning (FC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 69 publications
3
51
0
Order By: Relevance
“…The finding of dexamethasone facilitation of extinction supports recent results from a translational rodent model of PTSD-like behavior in which dexamethasone administration enhanced fear extinction and extinction retention in a dose-dependent manner (Sawamura et al, 2016). Additional studies in rodents have shown the efficacy of dexamethasone in decreasing FPS and contextual fear during fear extinction paradigms (Yang et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…The finding of dexamethasone facilitation of extinction supports recent results from a translational rodent model of PTSD-like behavior in which dexamethasone administration enhanced fear extinction and extinction retention in a dose-dependent manner (Sawamura et al, 2016). Additional studies in rodents have shown the efficacy of dexamethasone in decreasing FPS and contextual fear during fear extinction paradigms (Yang et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…In line with this hypothesis, a decrease in global methylation follows exposure of cultured cells to GR agonists, and these changes are accompanied by senescence-related alterations in gene expression and increased sensitivity of cells to oxidative stress (Bose et al, 2010;Bose et al, 2015). As we discussed above, glucocorticoids decrease DNA methylation via two distinct but synergistic mechanisms: 1) counteracting of mechanisms that maintain DNA methylation, resulting for example from decreases in the levels or activity of DNMT1 (Gassen et al, 2015;Yang et al, 2012); and 2) upregulation of enzymes involved in active demethylation, such as the Tet family of 5-methylcytosine dioxygenases (Bose et al, 2015;Sawamura et al, 2015). Stressors and glucocorticoids are not the only factors that impact these processes.…”
Section: As Summarized Inmentioning
confidence: 95%
“…This GR-induced demethylation is rapid and dynamic, suggesting that it is driven by active demethylating mechanisms. Indeed, exposure to glucocorticoids may upregulate enzymes involved in active demethylation, such as the Tet family of 5-methylcytosine dioxygenases in neuronal tissue (Bose et al, 2015;Sawamura et al, 2015). Nonetheless, glucocorticoids have also been shown to decrease in a dosedependent manner the expression of the gene encoding DNA methyltransferase 1 (DNMT1), the enzyme responsible for maintaining DNA methylation after cell division, in the mouse hippocampus .…”
Section: 'Stressing' the Epigenome: Focus On Glucocorticoid Signalingmentioning
confidence: 97%
“…A reduction in FKBP5 levels have been reported in PTSD patients (Yehuda et al 2009), and changes in methylation of the FKBP5 gene have been found in holocaust survivors and their offspring (Yehuda et al 2015a). Pretreatment with the synthetic corticosteroid dexamethasone prior to extinction not only rescued stress-induced fear extinction deficits but also regulated the expression of Fkbp5 mRNA and expression of the DNA methylation regulators Dnmt3a and 3b and Tet1, 2, and 3 (Sawamura et al 2016). The correlative data from this study demonstrate a pattern of Fkbp5 methylation linked to an accelerated extinction profile in an SEFL model, strengthening the notion that DNA methylation of key genes involved in both stress and memory may impact the degree of stress-enhanced fear learning, extinction, and retention.…”
Section: The Neuroepigenetics Of Stress-enhanced Fear Learningmentioning
confidence: 99%
“…For instance, SPS before fear conditioning results in a delayed extinction profile (Yamamoto et al 2009;Chauveau et al 2012;Sawamura et al 2016), an effect that can be rescued by treatment with an HDAC inhibitor (Matsumoto et al 2013). This is not surprising, given that HDAC inhibitors increase acetylation to support extinction learning and decrease anxiety in animal stress paradigms (Yamawaki et al 2012;Valvassori et al 2014).…”
Section: The Neuroepigenetics Of Stress-enhanced Fear Learningmentioning
confidence: 99%